A patient with spastic paralysis finally diagnosed as V180I genetic Creutzfeldt-Jakob disease 9 years after onset. Issue 1 (1st January 2020) - Nomura, Taichi; Iwata, Ikuko; Naganuma, Ryoji; Matsushima, Masaaki; Satoh, Katsuya; Kitamoto, Tetsuyuki; Yabe, Ichiro
ABSTRACT: Genetic Creutzfeldt-Jakob disease (gCJD) with a mutation in codon 180 of the prion protein gene (V180I gCJD) is the most common form of gCJD in Japan, but only a few cases have been reported in Europe and the United States. It is clinically characterized by occurring in the elderly and presenting as slowly progressive dementia, although it generally shows less cerebellar and pyramidal symptoms than sporadic CJD. Here, we report a patient with V180I gCJD who initially presented with slowly progressive spastic paralysis with neither cerebrospinal fluid (CSF) nor magnetic resonance imaging (MRI) abnormalities. His symptoms progressed gradually, and after 9 years, he displayed features more typical of CJD. Diffusion-weighted MRI revealed high-intensity signals in the cortical gyrus, and there was a marked increase of 14-3-3 protein and total tau protein in the CSF, but he was negative for the real-time quaking-induced conversion assay. Although the time course was more consistent with Gerstmann-Sträussler-Scheinker disease than CJD, genetic testing revealed V180I gCJD. This is the first report of a patient with V180I gCJD who initially presented with spastic paralysis, and also the first to reveal that it took 9 years from disease onset for cortical dysfunction to develop and for MRI and CSF abnormalities to be detectable. In conclusion, we should screen for V180I gCJD in elderly patients presenting with slowly progressive spastic paralysis.